SUPERVISI AKADEMIK : MENGURAI PROBLEMATIKA PROFESIONALISME GURU DI SEKOLAH - Munawar, Munawar (JURNAL AL-TANZIM, 2019)
This paper examines the principal's strategy in solving the problems of teacher professionalism through academic supervision. Academic supervision activities are a series of activities to help teachers explore and develop their competencies in order to manage learning activities well in order to achieve learning goals. This study is a literature review / research library where the data analysis is done through content analysis. The results of the study indicate that academic supervision activities carried out by the principal must begin with planning, implementation and evaluation with the principle of objectivity and continuous improvement. Through this, the professionalism of teachers in schools will be easily achieved and will be able to improve the quality of learning and the quality of educational institutions.